2018
DOI: 10.1016/j.ultsonch.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasonic as a novel technology for removal of inorganic scales (KCl) in hydrocarbon reservoirs: An experimental approach

Abstract: Inorganic scales are one of the most important causes of formation damage, which causes pressure drops near wellbores; these in turn impair permeability and severely reduce production in oil and gas reservoirs. This paper examines the effectiveness of ultrasonic waves in removing potassium chloride (KCl) scales. Twenty core samples with different permeabilities were exposed to KCl precipitation. After measuring the permeabilities of the saturated core samples, the samples were first subjected to water injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Sensitivity study on core permeabilities gave rise to the conclusion that the effect of ultrasound on NaCl removal in the pore channels are more significant in low permeability reservoirs. Identical results were observed by the same authors for the treatment of KCl scales using combined ultrasound and water injection [28].…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediasupporting
confidence: 84%
“…Sensitivity study on core permeabilities gave rise to the conclusion that the effect of ultrasound on NaCl removal in the pore channels are more significant in low permeability reservoirs. Identical results were observed by the same authors for the treatment of KCl scales using combined ultrasound and water injection [28].…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediasupporting
confidence: 84%
“…The authors suggested the increment in the US power in order to achieve better efficiency. However, increasing the US power above 1000 W has been reported to collapse core samples by Taheri Shakib et al [73] .
Fig.
…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
“…There are several studies that have attempted to improve the permeability and pore structure of porous media which have been damaged, and hence, improve the oil recovery of the reservoir [71] , [72] , [73] , [74] , [75] , [76] , [77] . Some of these studies have focused on the removal of inorganic salts causing formation damage in the near wellbore region ( Fig.…”
Section: Recent Progress In the Utilization Of Us In Oil Technologiesmentioning
confidence: 99%
See 2 more Smart Citations